Peran Kepala Sekolah dalam Membina Kompetensi Profesional dan Kinerja Guru di SMP Negeri 1 Betung Kabupaten Banyuasin - Chandra, Adi; Maulana, Maulana; Alamsyah, Alamsyah (Mahesa Research Center, 2023)
This article aims to analyze the role of school principals in developing professional competence and teacher performance at SMP Negeri 1 Betung, Banyuasin Regency. The problem focuses on the role of the principal in fostering professional competence and teacher performance at SMP Negeri 1 Betung, Banyuasin Regency, and supporting factors and inhibiting factors for the role of the principal in fostering professional competence and performance of teachers at SMP Negeri 1 Betung, Banyuasin Regency. This research uses qualitative methods with data collection techniques through observation, interviews and documentation studies. Data analysis was carried out using the interactive model from Miles and Huberman. The research results show that the role of the principal at SMPN 1 Betung, Banyuasin Regency in improving professional competence and teacher performance includes real roles as an educator, manager, supervisor, leader, innovator, and motivator. In addition, there are recommended roles such as classroom observation, individual talks, and coaching. The supporting factors for the role of the school principal are discipline, example, and kinship, while the inhibiting factors are the large number of teachers and limited learning infrastructure.